1990
DOI: 10.1159/000235274
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Anaphylactoid Response Induced in Rats by Castanospermine and Dextran

Abstract: The plant alkaloid castanospermine (10 mg/kg or higher, i.p.; 400 mg/kg, p.o.) induced in some rat strains an anaphylactoid reaction similar to that induced by dextran, i.e. erythema and edema of the snout, ears and paws, for several hours after administration. 86% of the rats from a responsive strain responded to castanospermine while 79% responded to dextran. Rats which responded to castanospermine showed marked, but transient, tachyphylaxis to a second dose of castanospermine or dextran. Rats maintained on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In order to increase RBC aggregation, we injected dextran 500. Doherty & Beaver (1990) found that dextran does not induce an anaphylactoid response in WISTAR rats.…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase RBC aggregation, we injected dextran 500. Doherty & Beaver (1990) found that dextran does not induce an anaphylactoid response in WISTAR rats.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion Metastasis 1998/99;18:192-197 193 tropic drug carriers are dextran based [4], and their testing in rodent models can overestimate the efficacy because most rodents have a dextran hypersensitivity leading to abnormal extravasation and subsequent accumulation in lymph nodes [7]. Although ideal model systems would employ human tumor xenografts, this requires the use of immunocompromised nude or SCID mice with altered lymph node function and architecture.…”
Section: Rodent Model To Evaluate Tumor Burdenmentioning
confidence: 99%